Overexpression of oilseed rape trehalose-6-phosphate synthesis gene BnaC02.TPS8 confers sensitivity to low nitrogen and high sucrose-induced anthocyanin accumulation in Arabidopsis - Yuan, Pan; Yu, Mingzhu; Liu, Haijiang; Hammond, John P.; Cai, Hongmei; Ding, Guangda; Wang, Sheliang; Xu, Fangsen; Wang, Chuang; Hong, Dengfeng; Shi, Lei (Planta, 2024)
Main conclusion Overexpression of BnaC02.TPS8 increased low N and high sucrose-induced anthocyanin accumulation. Anthocyanin plays a crucial role in safeguarding photosynthetic tissues against high light, UV radiation, and oxidative stress. Their accumulation is triggered by low nitrogen (N) stress and elevated sucrose levels in Arabidopsis . Trehalose-6-phosphate (T6P) serves as a pivotal signaling molecule, sensing sucrose availability, and carbon (C) metabolism. However, the mechanisms governing the regulation of T6P synthase (TPS) genes responsible for anthocyanin accumulation under conditions of low N and high sucrose remain elusive. In a previous study, we demonstrated the positive impact of a cytoplasm-localized class II TPS protein ‘BnaC02.TPS8’ on photosynthesis and seed yield improvement in Brassica napus . The present research delves into the biological role of BnaC02.TPS8 in response to low N and high sucrose. Ectopic overexpression of BnaC02.TPS8 in Arabidopsis seedlings resulted in elevated shoot T6P levels under N-sufficient conditions, as well as an increased carbon-to-nitrogen (C/N) ratio, sucrose accumulation, and starch storage under low N conditions. Overexpression of BnaC02.TPS8 in Arabidopsis heightened sensitivity to low N stress and high sucrose levels, accompanied by increased anthocyanin accumulation and upregulation of genes involved in flavonoid biosynthesis and regulation. Metabolic profiling revealed increased levels of intermediate products of carbon metabolism, as well as anthocyanin and flavonoid derivatives in BnaC02.TPS8- overexpressing Arabidopsis plants under low N conditions. Furthermore, yeast two-hybrid (Y2H) and bimolecular fluorescence complementation (BiFC) analyses demonstrated that BnaC02.TPS8 interacts with both BnaC08.TPS9 and BnaA01.TPS10. These findings contribute to our understanding of how TPS8-mediated anthocyanin accumulation is modulated under low N and high sucrose conditions.